RELASI JIHĀD DAN SABAR PERSPEKTIF MUḤAMMAD HUSEIN ṬABA’ṬABĀĪ DALAM TAFSIR AL-MIZĀN - Abdul Fatah (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2020)
This article figure out the concept of jihād and its correlation with the concept of patience through Muhammad Husein al-ṬabaṬaba’ī perspective. This research set out from a study that often separates the concept of Jihād from the concept of patience, which makes the understanding of jihād used as the basis for violence action in the Qur'an. Meanwhile, some jihād verses are often juxtaposed with patience.  By using the thematic interpretation research method (al-tafsīr al-maudū’ī) and Lucien Goldman's theory of genetic structuralism on the jihād and patient verses in Muhammad Husein al-Tabataba’ī’s Tafsīr, al-Mizān, this study found two conclusions: First, according to ṬabaṬabā’ī, jihād and patience have a strong correlation. Although jihād is a description of one’s faith, the greatest jihad is to be patient with the anger, lust and temptations of satan. A mujāhid is someone who has a patient nature in himself, so even jihād in the form of war must be done with patience. Second, from the analysis of genetic structuralism, the view of ṬabaṬaba’ī was come from an academic situation that emphasizes moderation and logical thinking. Thus, the jihād interpretation in the Tafsīr al-Mizān is peacefull Jihād.